2004
DOI: 10.1023/b:ddas.0000037822.55717.31
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Selectins, sICAM, sVCAM, and Angiogenic Proteins in Different Activity Groups of Patients with Inflammatory Bowel Disease

Abstract: The endothelium is involved in the pathogenesis of inflammatory bowel disease (IBD). So far knowledge of the precise role of soluble adhesion molecules and angiogenic factors at different periods of activity in IBD is scarce or contradictory. Our goal in this study was to determine the serum levels of adhesion molecules and angiogenic factors in IBD patients at different periods of disease activity--clinical remission, biochemical evidence of inflammation, and clinical evidence of activity. We used a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
2
36
0
2
Order By: Relevance
“…In previous studies, an increased expression of VEGF protein and VEGF mRNA in UC patients had already been observed in comparison with those found in healthy controls [25,[34][35][36][37][38]. Our results were consistent with those found in previous studies using active UC patient blood samples [25,34,35].…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, an increased expression of VEGF protein and VEGF mRNA in UC patients had already been observed in comparison with those found in healthy controls [25,[34][35][36][37][38]. Our results were consistent with those found in previous studies using active UC patient blood samples [25,34,35].…”
Section: Discussionsupporting
confidence: 93%
“…Vascular endothelial cell expression of E-selectin is entirely under transcriptional control, and cell surface expression can be detected approximately 2 hours after acute stimulation (29,31,32). In patients with IBD, both P-selectin and E-selectin have been shown to be constitutively expressed on inflamed vascular endothelium during the active phase of the disease (7,(33)(34)(35). Thus, both markers could be further evaluated as promising imaging biomarkers with In murine colitis models, it has been shown that FDG uptake was specifically correlated with glucose transporter 1 expression by CD4 + T cells, and those cells were identified as the major cellular source of FDG uptake in murine colitis (20).…”
Section: Discussionmentioning
confidence: 99%
“…P selectin is a member of the CAMs family mainly produced in PLT. A soluble fraction of P-selectin is also detected in patients with inflammatory disorders, including IBD, and possibly serves as selectin binding inhibitor [63] . The lectin containing N-terminal domain of P-selectin binds to P-selectin glycoprotein ligand (PSGL-1) found in leukocytes (mainly polymorphonuclears) mediating recruitment and rolling of infiltrating leukocytes in the gut mucosa, and initiating activation processes like chemokines production by monocytes and CD4(+) T-cells, as well as superoxide overexcretion by neutrophils [1] .…”
Section: Disease (N ) Hc (N ) Mpv Correlationsmentioning
confidence: 99%